EDUKASI KEAMANAN TRANSAKSI PERBANKAN DIGITAL MELALUI BLU by BCA - Syahira Khairunnisa; Amalia Kartika Sari; Nadatul Nikmah; Rolina Tua Br Sinaga; I. A. Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital banking has facilitated financial transactions, particularly among adolescents, while also increasing transaction security risks. This Community Service Program aims to improve adolescents’ understanding and awareness of digital banking transaction security through the blu by BCA service. The program was conducted through face-to-face educational activities involving 30 adolescents. The results indicate improved understanding and more cautious behavior in using digital banking services, highlighting the importance of security education in strengthening digital financial literacy and transaction safety.